A new numerical model for simulating top surface soil moisture and runoff. Issue 3 (8th May 2018) - Chen, Jiongfeng; Zhang, Wan-chang
Abstract : Purpose: This paper aims to construct a simplified distributed hydrological model based on the surveyed watershed soil properties database. Design/methodology/approach: The new established model requires fewer parameters to be adjusted than needed by former hydrological models. However, the achieved stream-flow simulation results are similar and comparable to the classic hydrological models, such as the Xinanjiang model and the TOPMODEL. Findings: Good results show that the discharge and the top surface soil moisture can be simultaneously simulated, and that is the exclusive character of this new model. The stream-flow simulation results from two moderate hydrological watershed models show that the daily stream-flow simulation achieved the classic hydrological results shown in the TOPMODEL and Xinanjiang model. The soil moisture validation results show that the modeled watershed scale surface soil moisture has general agreement with the obtained measurements, with a root-mean-square error (RMSE) value of 0.04 (m 3 /m 3 ) for one of the one-measurement sites and an averaged RMSE of 0.08 (m 3 /m 3 ) over all measurements. Originality/value: In this paper, a new simplified distributed hydrological model was constructed.